Wound Healing Activity of an Ointment from Solanum tuberosum L. "Tumbay Yellow Potato" on Mus musculus Balb/c - Rosas-Cruz G.P. (2020)
Background: Solanum tuberosum L. is an Andean tuber that is mainly characterized by its antioxidant properties. Objective: To evaluate the healing activity of an S. tuberosum-based ointment on wounds induced in mice. Material and methods: Ethanolic extracts of peel and pulp of tubers of S. tuberosum "Tumbay yellow potato"were prepared, which were incorporated into 1% and 2% ointment formulations. Mus musculus Balb/c with induced wound were distributed in the following working groups: Group I (Negative Control), Group II (Positive Control: Neomycin, Polymyxin B and Bacitracin Ointment) and Groups III and IV (Ointment at 1 % and 2% of S. tuberosum extract, respectively), daily administration of topical treatments were carried out for 07 days. Wound closure was determined during the experimentation time, then euthanized with sodium pentobarbital 60 mg/kg b.w. (i.p.) to obtain skin samples for histopathological analysis. Results: Groups III and IV showed that better evidence of wound closure and scarring in the histopathological analysis, the greatest effect being in Group IV. Conclusions: S. tuberosum ointments show healing activity in induced wounds in mice, the most effective treatment being the 2% ointment formulation. © 2020 Phcogj.Com.